SISTEM INFORMASI MANAJEMEN KREDIT BERBASIS WEB PADA BANK PERKREDITAN RAKYAT GEMILANG TEMBILAHAN - Muhammad Budiman; Ilyas (JURNAL PERANGKAT LUNAK, 2020)
BPR Gemilang Tembilahan is the only bank owned by the regional government of Indragiri Hilir, one of which has a financing product in the form of credit and currently the credit application and decision-making system in the credit committee is still not computerized because it still uses a manual system that is the use of paper in the credit application process and the committee process credit runs very long because not all credit committee members are in place and when an error occurs in recording in a bank's operational activities will be disrupted, as a result there are parties who feel disadvantaged, especially in the reporting process. Resulting in inaccurate and irrelevant data so that the service process will be hampered. Thus, the need for information systems that are increasingly increasing, it needs a good system in order to facilitate all processes. In this study the authors use the PIECES analysis method, to analyze the systems needed, the authors try to collect data by observation and direct interviews with the spaciousness found customers and bank leaders of BPR Gemilang Tembilahan. The design of this system uses the PHP programming language and XAMPP in processing or creating databases, dreamweaver for design and UML (Unified Modeling Language) for the system model. The results of this research are web-based Credit Submission Information Systems. With this system, it can speed up the credit application process and be more accurate in the information obtained.